2020
DOI: 10.1038/s41598-020-62141-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the short-term outcomes of using DST and PPH staplers in the treatment of grade III and IV hemorrhoids

Abstract: Stapled hemorrhoidopexy has a few advantages such as less postoperative pain and faster recovery compared with conventional hemorrhoidectomy. there are two major devices used for stapled hemorrhoidopexy, ppH stapler (ethicon endoSurgery) and DSt stapler (covidien). this study was conducted to investigate the postoperative outcomes among patients with grade iii and iV hemorrhoids who underwent hemorrhoidopexy with either of these two devices. A total of 242 consecutive patients underwent stapled hemorrhoidopexy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 38 publications
0
11
0
3
Order By: Relevance
“…For the remaining studies, the full texts were obtained and reviewed. Seven studies were excluded based on reasons listed in Table 1 [12][13][14][15][16][17][18]. Cumulatively, 17 articles (15 case reports and two case series) were considered relevant, and 38 patients were included ( Figure 1, Seven papers reported perirectal hematoma [3,17,18,[20][21][22][23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the remaining studies, the full texts were obtained and reviewed. Seven studies were excluded based on reasons listed in Table 1 [12][13][14][15][16][17][18]. Cumulatively, 17 articles (15 case reports and two case series) were considered relevant, and 38 patients were included ( Figure 1, Seven papers reported perirectal hematoma [3,17,18,[20][21][22][23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…For the remaining studies, the full texts were obtained and reviewed. Seven studies were excluded based on reasons listed in Table 1 [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Cumulatively, 17 articles (15 case reports and two case series) were considered relevant, and 38 patients were included ( Figure 1 , Table 2 ) [ 3 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has good overall results with very few side effects. [1][2][3][4] Studies suggested that, this model of treatment has various advantages over other conventional treatment methods. Few side effects which are most associated with this technique is postoperative pain but incidence rate of it is also very negligible.…”
Section: Introductionmentioning
confidence: 99%
“…Hemorrhoids are often referred to as hemorrhoidal disease (HD), are one of the most common anorectal diseases (1). The hemorrhoidal disease affects approximately 4.4-36 per cent of the general population, aged >50 years old (2,3). Hemorrhoids are clumps of tissue made up of muscle and elastic fibers and swollen, bulging blood vessels and supporting tissues that form in the anal canal of an individual.…”
Section: Introductionmentioning
confidence: 99%